A study of Financial Inclusion Through Pradhan Mantri Jan Dhan Yojana (PMJDY): A Case of Meerut District - Bagar, Vinod Kumar; Sijeriya, Rajeev (Journal of Commerce and Trade, 2020)
Indian planners since independence have tried to put financial inclusion at the centre of their policy. But despite nationalization of banks, establishment of cooperative societies, and many other such policies have not been able to substantially improve the livelihood of the poor. PMJDY was launched in 2014 as a comprehensive plan based on six pillars viz. Universal Access to Banking Facilities, Providing Basic Banking Accounts, Financial Literacy, Credit Guarantee Fund, Micro Insurance and Pension Scheme. The study investigates gender wise and caste wise differential among PMJDY account holders. The study is based on primary data for which a sample of 100 households was taken on a random basis. The results show a significant gender and caste wise differential with regard to transaction by self, awareness about DBT, savings, and receiving & activating Rupay debit card. Further, there exists caste wise but not gender wise differential because of motivation/reason behind opening an account in PMJDY and agreement on fulfillment of government's objectives. More than 80 percent of the respondents strongly agree/agree with the notion that they opened PMJDY account in anticipation that Rs.15 lakhs will be transferred into their account as promised by the present government. This simply shows the degree of political innocence of poor rural masses. Gender wise analysis clarifies that there exist a significant difference between male and female households in terms of multi dimensionally poor population but not on account of average intensity of deprivation. Classification-JEL : A12, V14